2012
DOI: 10.1186/1756-0500-5-507
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable endogenous control genes for microRNA expression profiling of childhood medulloblastoma and human neural stem cells

Abstract: BackgroundMedulloblastoma (MB) is the most common type of malignant childhood brain tumour. Although deregulated microRNA (miRNA) expression has been linked to MB pathogenesis, the selection of appropriate candidate endogenous control (EC) reference genes for MB miRNA expression profiling studies has not been systematically addressed. In this study we utilised reverse transcriptase quantitative PCR (RT-qPCR) to identify the most appropriate EC reference genes for the accurate normalisation of miRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 65 publications
0
21
1
Order By: Relevance
“…This difference is likely to be due to the different cell types used and the different experimental conditions. This may also explain the contrasting report by Genovesi et al (2012) on U6 snRNA in stem cells. Most of these studies have looked at endogenous controls in neuronal differentiation in cell lines whilst our study is focused on maturing neurons involved in synapse formation.…”
Section: Resultscontrasting
confidence: 42%
“…This difference is likely to be due to the different cell types used and the different experimental conditions. This may also explain the contrasting report by Genovesi et al (2012) on U6 snRNA in stem cells. Most of these studies have looked at endogenous controls in neuronal differentiation in cell lines whilst our study is focused on maturing neurons involved in synapse formation.…”
Section: Resultscontrasting
confidence: 42%
“…Numerous studies have demonstrated significantly altered miRNA expression patterns in types of human cancer, deregulation of miRNA expression and the contribution of miRNAs to the multistep processes of carcinogenesis either as oncogenes or as tumor-suppressor genes (8,9). A number of miRNA expression profiling studies have demonstrated that miRNA expression is dysregulated, by the comparison of MBs with normal cerebellum (10)(11)(12). A previous study determined that the expression of miR-17~92 was upregulated in MBs and promoted cell proliferation (13).…”
Section: Introductionmentioning
confidence: 99%
“…M -values were higher than expected (0.8–1.2) and they were even ranked differently on card A and card B. This might be due to intercard variability of snoRNAs as described by others37. In mRNA studies M -values should be less than 0.520.…”
Section: Discussionmentioning
confidence: 56%